Low human parvovirus B19 (B19V) DNA prevalence in blood donors from Central-West Brazil. Issue 4 (7th March 2019) - Slavov, Svetoslav Nanev; Gonçalves de Noronha, Lorena Aparecida; Gonzaga, Filipe Almeida Carvalho; Pimentel, Bárbara Maciel Sidou; Kashima, Simone; Haddad, Rodrigo
Abstract : Parvovirus B19 (B19V) transmission may occur through blood transfusion as a result of asymptomatic viral persistence in blood donors. Our study evaluated the prevalence and viral load of B19V in blood donors from Brasilia, Federal District, Central-West Brazil. B19V DNA detection and quantification were performed in 477 blood donors. The positive samples were also tested for anti-B19V IgG and haemoderivative recipients were investigated for adverse effects following transfusion. B19V DNA prevalence was 0.21  % ( n =1/477). The positive B19V DNA sample was also anti-B19 IgG-positive (probably persistent infection). The viral load was low and no adverse effects following blood transfusion were registered in the recipients. This study demonstrated that the B19V DNA prevalence in blood donors from Central-West Brazil is low. Nevertheless, the mere presence of B19V DNA in blood donors strengthens the need for viral molecular screening, especially in haemoderivatives that that will go to susceptible recipients.